RANCANG BANGUN SISTEM PENGERING GAPLEK TIPE HIBRIDA ANTARA EFEK RUMAH KACA (ERK) DAN TUNGKU BIOMASSA - Brahmantya Aji Pramudita; Bandiyah Sri Aprillia; Achmad Rizal (Politeknik Caltex Riau, 2020)
The greenhouse system works by utilizing solar thermal energy. It has a deficiency because it depends on weather to get maximum solar thermal energy. This deficiency can interfere with the drying process of plantation products, especially gaplek. Therefore, biomass furnace is added to overcome the dependence of solar thermal energy. The result of the proposed hybrid dryer system can control the temperature below 60℃. Moreover, the humidity can reach a minimum point of 60% while the temperature is 57℃. Those results show the system can give nomerous dry air to the dryer room because the greenhouse system is equipped with an exhaust fan. Thus, gaplek can appropriately dry according to the desired grade. Then, the cost of operating the proposed hybrid drying system is inexpensive, which is Rp 158.194,65 per year.